2020
DOI: 10.1017/mor.2019.51
|View full text |Cite
|
Sign up to set email alerts
|

Value Constraining or Value Enabling? The Impact of Business Group Affiliation on Post-Acquisition Performance by Emerging Market Firms

Abstract: Literature has advanced two contrasting theoretical perspectives related to the governance structure of business groups: the ‘value-constraining’ perspective, which focuses on principal–principal agency conflict and organizational inertia theory, and the ‘value-enabling’ perspective, which emphasizes the role of business groups in mitigation of institutional voids. Building on these two competing lenses, we develop hypotheses to examine post-acquisition performance of affiliate firms relative to stand-alone fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 129 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…Noting the unique governance structure adopted in Indian corporate sectors, we address business group affiliation as a dichotomous variable, equal to 1 if the firm is affiliated with a business group and 0 otherwise. Extensive literature attests to the influence of business groups on innovation (Mahmood et al, 2017; Popli & Ladkani, 2020) and sustainability initiatives (Ray & Chaudhuri, 2018). As another dichotomous variable, we account for family firm status based on shareholding patterns such that a firm is a family firm if the shares held by promoters are more than 20% (La Porta et al, 1999).…”
Section: Context Data and Resultsmentioning
confidence: 99%
“…Noting the unique governance structure adopted in Indian corporate sectors, we address business group affiliation as a dichotomous variable, equal to 1 if the firm is affiliated with a business group and 0 otherwise. Extensive literature attests to the influence of business groups on innovation (Mahmood et al, 2017; Popli & Ladkani, 2020) and sustainability initiatives (Ray & Chaudhuri, 2018). As another dichotomous variable, we account for family firm status based on shareholding patterns such that a firm is a family firm if the shares held by promoters are more than 20% (La Porta et al, 1999).…”
Section: Context Data and Resultsmentioning
confidence: 99%
“…In particular, the theory framework further suggests that agency conflict intensifies in establishing links between the firm ownership structure and internationalization decisions (Cuervo-Cazurra, Inkpen, Musacchio, & Ramaswamy, 2014). Indeed, the extant literature recognizes the importance of principal-principal conflict in emerging economies (Khanna & Palepu, 2000;Popli & Ladkani, 2020), and, more recently, have made more assumptions about the internalization process of different business groups (Gaur & Delios, 2015;Dau, Morck, & Yeung, 2021).…”
Section: Agency Theory and Internationalizationmentioning
confidence: 99%
“…In addition, active or passive government support, such as access to capital through loan guarantees and other favorable government policies favors companies to have access to the foreign market (Hennart et al, 2017). However, the agency problem between agents and owners might be aggravated by international diversification because foreign investments give administrators greater freedom to pursue their own interests compared to domestic investments (Cuervo-Cazurra, 2006;Popli & Ladkani, 2020). Recognizing this, research on the internationalization of business groups is still a topic that received less attention (Aguilera, Crespí-Cladera, Infates, & Pascual-Fuster, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Different elements from unrelated fields stimulate people to assess problems from a new perspective and to use old resources in a new way (Burt, 1992). Popli and Ladkani (2020) have shown that greater group diversification leads to more robust post-acquisition performance for affiliate acquirers.…”
Section: Resource Mobilization and Heterophily In The Chinese Vc Indu...mentioning
confidence: 99%